Targeting phosphorus recovery from sewage sludge while preventing contaminant spread via combined hydrothermal carbonization and wet chemical extraction - Boniardi, G.; Sessolo, L.; Gelmi, E.; Turolla, A.; Canziani, R. (Separation and purification technology, 2024)
•P extraction from slurry and hydrochar is feasible, being the second more convenient.•Oxalic acid proved a good leaching agent and a more environmentally friendly acid.•Selection of the best leaching agent is related to characteristics of source material.•Material recovered from hydrochar was compliant with EU regulation on fertilizers.•High Fe and Al content in the source material may require additional treatments. The increasing production of sewage sludge is making its management more challenging than ever. Increasing costs of handling and disposal promoted the development of alternative thermochemical treatments for combining waste management and resource recovery such as the hydrothermal carbonization. The products of this process are an interesting source of phosphorus, which is subject to depletion in the next future. This work investigates at the laboratory scale the phosphorus recovery via wet chemical extraction from slurry and hydrochar as the extraction and precipitation of (heavy) metals and metalloids to promote the recovery of non-contaminated high-value phosphorus-rich products. Experimental results indicated that both matrices performed well in terms of phosphorus recovery and acid consumption, but the maximum overall recovery efficiency was higher when phosphorus was extracted from the hydrochar (49.6–75.1%) by using oxalic, sulfuric and nitric acids. Oxalic acid resulted as the most promising extractant from slurry at a dosage of 40 g/L. Instead, extraction from hydrochar was less affected by the type of acid used, suggesting the role of pH as the main driver. The co-precipitation of metals and metalloids was higher in slurry, with one sample of the recovered material exceeding the threshold limits of European fertilizer regulation. Instead, recovered material obtained from hydrochar showed lower level of contamination (in terms of Al, Fe, Ni, Cr and As content) and were regulatory compliant. This study attempts to guide the the type of acid and precipitants’ selection to address a good trade-off between a high P content and a low contamination in the recovered material.